Letter : International Solidarity Fund - Allen, W. H.
030-0048-001 The Association of Engineering & Shipbuilding Draughtsmen. Registered under T.U. Acts No. 1691 T. Please address all communications for Head Office to "The General Secretary." General Secretary : PETER DOIG Head Office : 96 ST GEORGE' S SQUARE, LONDON, S. W. 1 Telegraphic Address "DRAFTINEER, CHURTON, LONDON." Telephone —Victoria 2850 Enclosures Your Ref. Our Ref. 146, Burghead Drive, Glasgow, S.W.1 29th. Sept. 1938. No.1 District. Sir Walter Citrine, K.B.E. Smith Square, London. Dear Sir, International Solidarity Fund. At a recent meeting of the District Council of above Association (Scotland) it was decided that an effort should be made amongst the Scottish branches to encourage the collection of funds for relief of distress in Spain. I was instructed to request you to assist us to carry the proposal into effect. It was thought that there might be some form of official collecting cards which we could distribute amongst the branches. If there are such I shall be glad to have a supply. At the moment I cannot say how many will be required as it will depend upon the reception of the suggestion by our members. Please therefore, send me four dozen to start with and I shall ask for a further supply if required. Yours sincerely, W.H. Allen Hon. Secretary, No.1 District. 292/946/30/48